Implementation of the house assimilation policy through the involvement of community counselors in Padang correctional center, Indonesia - Khaidir, Afriva; Salsabila, Aisha Hani; Yusran, Rahmadani; Alhadi, Zikri (Kasetsart Journal of Social Sciences, 2026)
This study aims to describe the Implementation of the House Assimilation Policy through the Involvement of Community Counselors in Padang Correctional Center, Indonesia. This study is a type of qualitative research using descriptive methods, and the selection of informants in this study used purposive sampling techniques. Interviews, observations, and documentation were carried out as the data collection technique for this study. Ten informants were selected from Prison Management, Community Counselors, and Clients. The results of this study found that the implementation of the housing assimilation policy can be explained as follows: first, serving correctional clients to fulfil mandatory reporting requirements. Second, coordinating with families and local government officials within the supervision framework for correctional clients. Third, providing motivation and assistance to clients facing challenges. Fourth, implementing specialised activities for correctional clients has also been carried out smoothly. Fifth, conducting community research by officers has been carried out well.